A NOVEL BIOLOGICAL DOSIMETRY ASSAY AS A POTENTIAL TOOL FOR TRIAGE DOSE ASSESSMENT IN CASE OF LARGE-SCALE RADIOLOGICAL EMERGENCY. Issue 1 (6th February 2019) - Testa, A; Palma, V; Patrono, C
Abstract: In case of mass radiological emergencies, new strategies involving biological and clinical endpoints are requested for an efficient triage classification of casualties. For this purpose, we developed a novel protocol combining the two most established cytogenetic methods used in biological dosimetry (dicentric and micronucleus assays) into a single one, in order to have a time-saving, inexpensive and potentially automatable instrument to be used for triage purposes in case of large-scale radiological events. This method could be considered as a 'three in one' assay allowing the simultaneous scoring of chromosome aberrations and micronuclei on a single slide, and also enabling to discriminate between metaphases in first and second cell division without the Fluorescence plus Giemsa staining. This method needs further validation through inter-comparisons involving biological dosimetry laboratories, to verify its reproducibility. Moreover, the possibility to apply the already existing software for automation for dicentric and micronucleus assays could be also verified.